The informative treatment of the 2007 Pisco earthquake in the newspapers El Comercio, La República and El Peruano - Santos Chaparro, Luis Martín (2024)
Major earthquakes are events that put a country's public and private institutions to the test. Each event leads to analysis, debate, and reflection on the response capacity of the various fields of action, including the media. The objective of this article is to analyze the informative treatment of the newspapers El Comercio, La República and El Peruano of the Pisco earthquake of August 15, 2007 - with the theoretical foundations of Agenda-Setting and Framing - to determine the predominance of topics, approaches, social groups, and their roles as protagonists-secondary and patient-agents. The quantitative method was applied to relate variables and an analysis sheet was used for data collection. The sample, non-probabilistic, comprised only the copies of the print run distributed in the city of Lima during the 15 days following the earthquake. The results show that the following approaches stand out: Description of pain and solidarity, Rehabilitation and reconstruction, Balance of damages, Civil and administrative liability, which shows that the coverage was focused on the consequences of the earthquake, the response actions, and the efficiency or not of the executing entities. This study derives from the author's research for his master's thesis in Communications at the Universidad Nacional Mayor de San Marcos.